Modelling of the behaviour of steel fibre reinforced concrete (SFRC) beams - Lim, Wei Qing (2014)
Concrete has the lowest ratio between cost and strength as compared to others available materials and hence it is still the most widely used materials in construction. However, the brittle behaviours of concrete has affected the reliability and durability of structures. So, steel fibres are suggested adding into conventional concrete to improve the structural behaviours. The structural behaviours of two-span continuous steel fibre reinforced concrete (SFRC) beam were studied in present investigation using non-linear finite-element analysis. Finite element program, Abaqus was adopted to perform the finite element analysis of present investigation. The effects of steel fibres in concrete were modelled by SFRC constitutive model proposed by Lok and Xiao (1999). Initially, the validation and calibration works FE predictions were performed by using experimental results. After the good correlation among FE predictions and experimental results were achieved, parametric modelling was carried out using by two key parameter; stirrups spacing (i.e. stirrups spacing increment, SI) and fibre contents (i.e. volume fraction, Vj). The settings were designed to examine the potential of steel fibres to serve as a part of stirrups. Beside these, other key structural parameter included strength, ductility, cracking propagation and modes of failure were determined through the investigation. The findings showed that the mentioned structural behaviours of beam were improved by inclusion of steel fibres significantly at an optimum amount of fibres dosage.